Role of TNF-Alpha, IFN-Gamma, and IL-10 in the Development of Pulmonary Tuberculosis - Cavalcanti, Yone Vila Nova; Brelaz, Maria Carolina Accioly; Neves, Juliana Kelle de Andrade Lemoine; Ferraz, José Candido; Pereira, Valéria Rêgo Alves (Pulmonary Medicine, 2012)
Host immune response against Mycobacterium tuberculosis is mediated by cellular immunity, in which cytokines and Th1 cells play a critical role. In the process of control of the infection by mycobacteria, TNF-alpha seems to have a primordial function. This cytokine acts in synergy with IFN-gamma, stimulating the production of reactive nitrogen intermediates (RNIs), thus mediating the tuberculostatic function of macrophages, and also stimulating the migration of immune cells to the infection site, contributing to granuloma formation, which controls the disease progression. IFN-gamma is the main cytokine involved in the immune response against mycobacteria, and its major function is the activation of macrophages, allowing them to exert its microbicidal role functions. Different from TNF-alpha and IFN-gamma, IL-10 is considered primarily an inhibitory cytokine, important to an adequate balance between inflammatory and immunopathologic responses. The increase in IL-10 levels seems to support the survival of mycobacteria in the host. Although there is not yet conclusive studies concerning a clear dichotomy between Th1 and Th2 responses, involving protective immunity and susceptibility to the disease, respectively, we can suggest that the knowledge about this responses based on the prevailing cytokine profile can help to elucidate the immune response related to the protection against M. tuberculosis.